Persepsi dan Keterlibatan Auditor Internal terhadap Perilaku Etis Auditor Internal: Peran Mediasi Kolaborasi Three Lines dan Praktik GRC - Novi Kurniawan; Adela Nadya; Tan Ming Kuang (Owner : Riset dan Jurnal Akuntansi, 2026)
The study aims to examine how Internal Auditors’ Perception and Internal Auditors’ Engagement influence Three Lines Collaboration and Governance, Risk, and Compliance (GRC) Practices, and how these mechanisms relate to the Ethical Behavior of Internal Auditors in Indonesia. Prior evidence has predominantly positioned the Three Lines Model and GRC as organizational-level structural arrangements, leaving limited understanding of how internal auditors’ individual attributes shape collaborative governance quality and ethical conduct. Distinct from research that emphasizes formal structures and procedures, this study contributes by foregrounding internal auditors as individual actors and by positioning perception and engagement as determinants of Three Lines Collaboration and GRC Practices with implications for ethical behavior in internal auditing. Data were collected using a structured questionnaire from internal auditors directly involved in internal auditing, internal control, risk management, and compliance functions across various organizations, yielding 270 valid responses selected through purposive sampling. The hypotheses were tested using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that Internal Auditors’ Perception and Internal Auditors’ Engagement have positive and significant effects on Three Lines Collaboration and GRC Practices. Furthermore, Three Lines Collaboration and GRC Practices have a positive and significant effect on the Ethical Behavior of Internal Auditors. Overall, the findings suggest that strengthening internal auditors’ role-related perception and sustaining engagement are strategic levers to reinforce collaborative governance and embed ethical standards within organizations.